Predicting Caregiver Burden in Informal Caregivers for the Elderly in Ecuador - Pablo Ruisoto (International Journal of Environmental Research and Public Health, 2020)
Informal caregivers are the main providers of care for the elderly. The aim of this study is to examine the predictive value of different variables regarding caregivers and their elderly patients with respect to the caregiver’s burden. A convenience sample of 688 informal caregivers and 688 elderly people from Ecuador was surveyed. Only households with one caregiver and one elderly person were considered for the study. For informal caregivers, the following standardized measures were obtained: burden (Zarit Burden Interview), neuroticism (Eysenck Personality Questionnaire Revised-Abbreviated, EPQR-A), caregiver’s general health (GHQ-12), and social support (modified Duke-UNC Functional Social Support Questionnaire, FSSQ11). For the elderly, we employed standardized measures of cognitive function (short portable mental status questionnaire, SPMSQ), Pfeiffer’s test, and functional dependency (Barthel scale/Index, BI). Females were over-represented in caregiving and reported significantly higher burden levels than those of males. In both male and female caregivers, the burden was best predicted by the time of caring, neuroticism, and elderly cognitive impairment. However, some predictors of burden were weighted differently in males and females. The functional independence of the elderly was a significant predictor of burden for male caregivers but not females, while caregiver competence was a significant predictor for females but not males. These variables accounted for more than 88% of the variability in informal caregivers.